Novel coronaviruses and mammarenaviruses of hedgehogs from Russia including the comparison of viral communities of hibernating and active specimens - Lukina-Gronskaya, A. V.; Chudinov, I. K.; Korneenko, E. V.; Mashkova, S. D.; Semashko, T. A.; Sinkova, M. A.; Penkin, L. N.; Litvinova, E. M.; Feoktistova, N. Yu; Speranskaya, A. S. (Frontiers in Veterinary Science, 2024)
IntroductionSmall mammals, especially rodents and bats, are known reservoirs of zoonotic viruses, but little is known about the viromes of insectivorous species including hedgehogs (order Eulipotyphla), which often live near human settlements and come into contact with humans.MethodsWe used high-throughput sequencing and metaviromic analysis to describe the viromes of 21 hedgehogs (Erinaceus sp.) sampled from summer 2022 to spring 2023. We captured 14 active animals from the wild (seven in European Russia and the other seven in Central Siberia). The remaining 7 animals were hibernating in captivity (captured in European Russia before the experiment).Results and discussionThe diversity of identified viral taxa as well as the total number of reads classified as viral was high in all active animals (up to eight different viral families per animal), but significantly lower in hibernating animals (zero or no more than three different viral families per animal). The present study reports, for the first time, betacoronaviruses and mammasrenaviruses in hedgehogs from Russia. Erinaceus coronaviruses (EriCoVs) were found in 4 of 7 active animals captured in the wild, in European Russia, making it is the easiest finding of EriCoVs in Europe. One animal was found to carry of two different EriCoVs. Both strains belong to the same phylogenetic clade as other coronaviruses from European hedgehogs. Pairwise comparative analysis suggested that one of these two strains arose by recombination with an unknown coronavirus, since all of identified SNPs (n = 288) were found only in the local genome region (the part of ORF1b and S gene). The novel mammarenaviruses (EriAreVs) were detected in 2 out of 7 active and in 2 out of 7 hibernating animals from the European Russia. Several complete L and S segments of EriAreVs were assembled. All identified EriAreVs belonged to the same clade as the recently described MEMV virus from Hungarian hedgehogs. As the hibernating hedgehogs were positive for EriAreVs when kept in controlled conditions without contact with each other, we suggest the possibility of persistent arenavirus infection in hedgehogs, but further experiments are needed to prove this.